Viability of Human Adenovirus from Hospital Fomites - Ganime, Ana Carolina (2014)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Virologia Comparada e Ambiental. Rio de Janeiro, RJ, Brasil.